2022
DOI: 10.3390/bioengineering9090444
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-Induced Amplitude Modulation of Forcecardiography Signals

Abstract: Forcecardiography (FCG) is a novel technique that records the weak forces induced on the chest wall by cardio-respiratory activity, by using specific force sensors. FCG sensors feature a wide frequency band, which allows us to capture respiration, heart wall motion, heart valves opening and closing (similar to the Seismocardiogram, SCG) and heart sounds, all simultaneously from a single contact point on the chest. As a result, the raw FCG sensors signals exhibit a large component related to the respiratory act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Forcecardiography is a novel technique based on specific wearable force sensors that measure the local forces induced on the chest wall by the mechanical activity of the heart and lungs [ 110 , 111 , 112 , 113 , 114 , 115 ]. FCG signals were first acquired by means of sensors based on force-sensing resistors (FSR), which have already proved suitable for muscle contraction monitoring [ 116 ], gesture recognition [ 117 ], and the control of biosignal-based human–machine interfaces [ 118 ], such as the “Federica Hand” prosthesis [ 119 , 120 , 121 , 122 ] and an upper-limb exoskeleton [ 123 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forcecardiography is a novel technique based on specific wearable force sensors that measure the local forces induced on the chest wall by the mechanical activity of the heart and lungs [ 110 , 111 , 112 , 113 , 114 , 115 ]. FCG signals were first acquired by means of sensors based on force-sensing resistors (FSR), which have already proved suitable for muscle contraction monitoring [ 116 ], gesture recognition [ 117 ], and the control of biosignal-based human–machine interfaces [ 118 ], such as the “Federica Hand” prosthesis [ 119 , 120 , 121 , 122 ] and an upper-limb exoskeleton [ 123 ].…”
Section: Methodsmentioning
confidence: 99%
“…The morphological similarity between the PW signals provided by the PPG and FCG sensors was quantitatively assessed by evaluating their normalized cross-correlation (NCC) [ 110 , 111 , 112 , 113 , 114 , 115 ]. In particular, NCC was computed both between single corresponding heart beats and between whole signal segments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication [ 83 ], a retrospective analysis of the FCG signals acquired in [ 23 ] was carried out to analyze the relationship between the amplitude variations in the dHF-FCG component and the respiratory activity. In [ 23 ], six healthy volunteers were involved who were asked to stay at rest and in a seated position while breathing at a quite pace.…”
Section: Introductionmentioning
confidence: 99%
“…The FCG signals were acquired via a piezoelectric FCG sensor, presented precisely in [ 23 ], which had been placed on the chest of the subjects at the point of maximal impulse (see Figure 1 ) via medical adhesive tape and then fastened with a belt around the thorax. The retrospective analysis presented in [ 83 ] showed that respiration causes amplitude modulations of the dHF-FCG component. This finding was in agreement with the existing literature on respiratory-induced changes in SCG signals [ 71 , 73 , 74 , 75 , 76 ] and provided further evidence of the close matching between the information content of dHF-FCG and SCG signals.…”
Section: Introductionmentioning
confidence: 99%